Criação de valor e engajamento do funcionário: um estudo no setor público municipal na percepção dos stakeholders - Martinez, Fernanda dos Santos (2022)
The concept of creating public value is one of the topics that has been generally studied today. In this sense, public value has become, over time, of interest to society and scholars in the area (MEYNHARDT and JASINENKO, 2020). The present study has the general objective of identifying how the creation of public value affects the perception of stakeholder engagement. As specific objectives, the study proposes to: evaluate the perception of stakeholders regarding the creation of value; assess stakeholder perceptions of engagement and verify how value creation is related to engagement. This is a descriptive and quantitative research. The public of the present study were 226 public servants of a Municipal administration in the State of Rio Grande do Sul (RS). Data collection took place through the application of a questionnaire composed of three parts: Public Value Scale (EVP), Utrecht Work Engagement Scale (UWES) and characterization of the respondents' profile. Thus, first, the questionnaires were submitted to the face (or content) analysis process, with translation of the questionnaires, review by experts and pre-test. Afterwards, the data were submitted to descriptive statistics, correlation and regression analysis. In the results, the data showed that in the general characterization of the sample profile, the majority are male, aged between 48 and 54 years, and, as far as schooling is concerned, they have a degree. It was observed that three dimensions of public value creation and three items showed a positive and significant relationship in relation to work engagement. In this way, it was possible to verify that the creation of public value impacts on engagement at work. Finally, the present study aimed to contribute both in the practical and theoretical spheres. In the practical scope, through the measurement of the impact generated by the public organization, it was possible to verify that there was a creation of public value and engagement at work. In the theoretical sphere, it aimed to contribute to the literature on the topics of public value creation and Stakeholder management, engagement in work in the public sector.